2006
DOI: 10.3892/ijo.28.6.1317
|View full text |Cite
|
Sign up to set email alerts
|

Biology of insulin-like growth factor binding protein-4 and its role in cancer (review)

Abstract: Insulin-like growth factor binding protein-4 (IGFBP-4) is an important member of the insulin-like growth factor (IGF) system. The IGFBP-4 has three domains of which the N-terminal sequence is important for the binding of IGF. It acts as a transport protein for IGF-I and IGF-II and modulates their biological effects. There is increasing evidence that IGFBP-4 inhibits IGF-induced cellular growth both in vitro and in vivo. IGFBP-4 can also mediate its actions through a mechanism independent of IGFs. IGFBP-4 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 104 publications
1
80
0
1
Order By: Relevance
“…The identification of IGFBP-4 as an inhibitor of Wnt/b-catenin signalling may also have some implications for cancer biology 16 . It was shown that treatment with IGFBP-4 reduces cell proliferation in some cancer cell lines in vitro, and that overexpression of IGFBP-4 attenuates the growth of prostate cancer in vivo.…”
mentioning
confidence: 99%
“…The identification of IGFBP-4 as an inhibitor of Wnt/b-catenin signalling may also have some implications for cancer biology 16 . It was shown that treatment with IGFBP-4 reduces cell proliferation in some cancer cell lines in vitro, and that overexpression of IGFBP-4 attenuates the growth of prostate cancer in vivo.…”
mentioning
confidence: 99%
“…It was reported in inhibiting colon cancer growth (7,15 (9). Salinomycin has been evaluated by several studies in various types of cancer stem cells (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with IGFBP-4 reduces cell proliferation in some cancer cell lines in vitro, and overexpression of IGFBP-4 attenuates the growth of prostate cancer in vivo (Durai et al 2006).…”
Section: Igfbp-4mentioning
confidence: 99%